Can we make a star on Earth - Bradshaw, Gideon (London : BBC, 2009)
Nuclear fusion has kept our Sun burning for five billion years. Might it be harnessed here on Earth as an energy source? This program illustrates the race to create artificial stars that can ensure humanity's earthbound survival. Several facilities and projects are profiled-including the Joint European Torus, or JET, which initiates nuclear fusion at a rate far higher than that inside the Sun; a bigger version of JET known as ITER, now under construction in southern France; an American approach known as inertial fusion underway at the National Ignition Facility in California; and the so-called Z-Machine in New Mexico, designed to produce astronomically high temperatures and, possibly, the birth of a star-like object
Camera, Kevin White ; sound, George McMillan ; production coordinator, Donna Dixon ; editor, Martin Johnson
dvd format
Keywords: Nuclear fusion; Controlled fusion; Power resources; Sun -- Research